More rapid polar ozone depletion through the reaction of HOCl with HCl on polar stratospheric clouds - Prather, Michael J. (1992)
The direct reaction of HOCl with HCl is shown here to play a critical part in polar ozone loss. Observations of high levels of OClO and ClO in the springtime Antarctic stratosphere confirm that most of the available chlorine is in the form of ClO(x). But current photochemical models have difficulty converting HCl to ClO(x) rapidly enough in early spring to account fully for the observations. Here, a chemical model is used to show that the direct reaction of HOCl with HCl provides the missing mechanism. As alternative sources of nitrogen-containing oxidants have been converted in the late autumn to inactive HNO3 by known reactions on the sulfate layer aerosols, the reaction of HOCl with HCl on polar stratospheric clouds becomes the most important pathway for releasing that stratospheric chlorine which goes into polar night as HCl.